Taxonomic review of Ctenodontina Enderlein, 1914 with the revalidation of Catostola Hull, 1958 (Diptera: Asilidae: Asilinae) and description of a new species - Camargo, Alexssandro; Vieira, Rodrigo; Rafael, José Albertino (Zootaxa, 2023)
A taxonomic review of Ctenodontina Enderlein, 1914, was performed and only two species are included: Ctenodontina mochica Lamas, 1973 and Ctenodontina pectinatipes Enderlein, 1914. Catostola Hull, 1958 stat. rev., a genus that was previously allocated as junior synonym of Ctenodontina has its status revalidated and justifications for this nomenclatural act are presented. Consequently, seven species previously allocated in Ctenodontina were transferred to Catostola stat. rev.: Catostola baleta (Walker, 1849) comb. nov., Catostola carrerai Hull, 1958 comb. rev., Catostola complicata (James, 1953) comb. nov., Catostola martini (Fisher, 1992) comb. nov., Catostola maya (Carrera & d’Andretta, 1953) comb. rev., Catostola nairae (Vieira, 2012) comb. nov., and Catostola sagta (Vieira, Ayala-Landa & Rafael, 2017) comb. nov. All species were redescribed and illustrated, except Catostola carrerai Hull, 1958 comb. rev., and Ctenodontina mochica Lamas, 1973, for which only diagnosis were provided. A new species Catostola indecisa sp. nov., was described and illustrated. In addition, new distribution records were provided for Catostola baleta comb. nov., Catostola martini comb. nov., Catostola maya comb. rev., Catostola nairae comb. nov., and Catostola sagta comb. nov. An identification key to all species is provided including distribution maps with previous and new records.